Adiwiyata Program Management in MIN 7 Medan City - Yusuf Hadijaya; Muhammad Nurul Fadhli (STAI Miftahul Ula Nganjuk, 2022)
This research aims to describe how Adiwiyata program management at MIN 7 Medan City. The problem focus in this research is the Adiwiyata Program Management Function at MIN 7 Medan City. This research used qualitative research methods and documentation studies. The findings of this study are: (1) Planning for the Adiwiyata program at MIN 7 Medan City is carried out by involving all Madrasah residents. Establishing the vision and mission of the Madrasah, assessing the environment around the Madrasah and formulating a strategy for implementing the Adiwiyata program; (2) The organization of the Adiwiyata program at MIN 7 Medan City is as follows: The head of the Madrasah acts as a coach and so onwards the structure of the Adiwiyata team consisting of the Deputy Head of Madrasah, all teachers and staff and students. After compiling the team, the main tasks and functions of each are determined according to the field. There are also collaborations with various parties related to the Adiwiyata program; (3) The implementation of the Adiwiyata program at MIN 7 Medan City has been carried out by involving all Madrasah residents, implementing environmental-based adiwiyata madrasa policies. Madrasas also organize several activities to create a clean and healthy environment, implementation of the Adiwiyata Madrasah environment-based curriculum, implementation of participatory-based environmental activities as well as implementation of environmentally friendly facilities management; (4) Supervision of the Adiwiyata program at MIN 7 Medan City is carried out every day by all Madrasah residents, evaluated in monthly meetings. The Adiwiyata implementation is reported by the Adiwiyata Team to the Head of Madrasah; and (5) Supporting Factors for the Adiwiyata Program at MIN 7 Medan City are the guidance of the Environmental Service, Leadership of the Head of Madrasah, Team solidity, students are easy to direct and support from Madrasah partners, while the Inhibiting Factors for the Adiwiyata Program at MIN 7 Medan City are limited funds, down enthusiasm, takes a lot of time and energy